PENGARUH INFLASI, HARGA MINYAK MENTAH DAN SUKU BUNGA THE FED TERHADAP SUKU BUNGA BANK INDONESIA - Elisabeth Maria Saru Dua Moong; Sugeng Setyadi; M. Sabeth Abilawa (Jurnal Ekonomi-Qu, 2017)
The aim of this research is to prove the influence of inflation, crude oil price and Fed Fund Rate to BI Rate. The data are monthly time series from 2010:01-2016:06. The data are collected from Bank Indonesia, Indonesia Ministry of Energy and Mineral Resources and Federal Reserve Bank of St. Louis. Methodology of this research used Error Correction Model (ECM). The result show that simultaneous test (F-test) indicating that inflation, crude oil price and Fed Fund Rate  have significant effect on BI Rate simultaneously. Partial test (t-test) indicating that inflation have significant and positive effect on BI Rate, while crude oil price and Fed Fund Rate have significant and negative effect on BI Rate in long term. While in the short term indicating that Fed Fund Rate have significant and negative  effect on BI Rate. Inflation and crude oil price have insignificant effect on BI Rate in the short term.